Justice and community or communal law in Peru’s history - Peña Jumpa, Antonio (2018)
What is the origin and the foundations of Justice and Community or Community Law in Peru?.In the present article, the author studies the origins of the aforementioned concepts mentioned in several communities, supporting in pre-Inca history and other tools.The focus of this study is two basic institutions: the family and the community as well as some expressions in the community and the social ordering; finally, it presents a balance of the institutions addressed.